Karakter Pemimpin Zalim: Dalam Penjelasan Hadis Nabi - Ardiansyah Ardiansyah (Kependidikan Islam Fakultas Agama Islam, 2023)
It is sunnatullah that in life there are those who lead and those who are led. Between the leader and the led have a symbiotic relationship-mutualism or need each other. Learning from past history is a shared obligation to choose the ideal character of a leader in accordance with the traditions of the Prophet. This paper uses a type of qualitative research (Library Research) with a hadith thematic approach, the hadiths are traced using the syamilah maktabah to obtain data related to a predetermined theme, then conduct content analysis to obtain overall results and conclusions. The results of the research show that the hadiths found lead to the conclusion that tyranny is a very big sin, the characteristics of a leader who is unjust to his people is a disgraceful act.